A Study on Prevalence of Behavioral Disorders in Primary School Students in Abhar - Hassan Shams-Esfandabadi; Souzan Emami-Pour; Seyyed Jalal Sadrosadat (University of Social Welfare and Rehabilitation Sciences, 2003)
Objective: The purpose of the present study was to investigate the prevalence of behavioral disorder among of primary school students in Abhar. Materials & Methods: 600 primary school students (300 boys and 300 girls) of public primary schools in Abhar, Iran were used as the sample for this study. Their behavioral disorder scores were obtained by means of Rutter's teachers' questionnaire. Results: Using a cutpoint of 9, the prevalence rate of behavioral disorder was 43.3% among subjects, with boys showing higher rates of behavioral disorder (44.7%) than girls (42%) but no significant differences were found by gender on rates of behavioral disorders. 6.3 percent of the subjects had severe behavioral disorder. Conclusion: Academic achievement was negatively related to behavioral disorder. Significant differences were found by mothers' education on children's rates of behavioral disorder. Significant differences were found by fathers' occupation on children's rates of behavioral disorder.